Analisis Faktor-Faktor yang Mempengaruhi Pendapatan Nelayan Kerang di Wilayah Tanjung Balai, Sumatera Utara - Rr Dyah Paramitha Mentari; Zhulian Hikmah Hasibuan; Yedi Wihardi; Riya Liuhartana Nasyirudin Fuhrmann (Jurnal Bisnis, Manajemen, dan Ekonomi, 2026)
The purpose of this study is to determine the most important factor affecting the revenue of shellfish fishermen in Tanjung Balai City, North Sumatra.The study uses a survey method with 60 respondents and a quantitative approach. Primary data were collected through questionnaires and interviews, while secondary data were obtained from relevant institutions and literature. Data analysis was conducted using multiple linear regression.The results show that partially, capital, fishing duration, and selling price of shellfish have a positive and significant effect on fishermen's income, while fishing experience has no significant effect. Simultaneously, all independent variables significantly influence fishermen’s income, with a coefficient of determination (R²) of 0.68, indicating that 68% of income variation can be explained by the model. The most dominant factor affecting income is the selling price of shellfish, which is highly influenced by market conditions and seasonal changes.The average monthly income of shellfish fishermen is IDR 3,500,000, indicating relatively low, fluctuating income levels. This condition is influenced by limited capital, dependence on weather conditions, and unstable market prices. Therefore, policy support such as access to capital, price stabilization, and improvement in technology and fishermen capacity is needed to enhance the welfare of coastal communitie